\(\frac{2a}{3b}=\frac{3b}{4c}=\frac{4c}{5d}=\frac{5d}{2a}\)
nên theo tính chất dãy tỉ số băng nhau, ta có:
\(\frac{2a}{3b}=\frac{3b}{4c}=\frac{4c}{5d}=\frac{5d}{2a}=\frac{2a+3b+4c+5d}{3b+4c+5d+2a}=1\)
=> \(2a=3b=4c=5d\)
=> \(\frac{2a}{3b}+\frac{3b}{4c}+\frac{4c}{5d}+\frac{5d}{2d}=1+1+1+1=4\)
Đặt \(\frac{2a}{3b}=\frac{3b}{4c}=\frac{4c}{5d}=\frac{5d}{2a}=t.\)
\(\Rightarrow2a=3b.t\)
\(\Rightarrow3b=4c.t\)
\(\Rightarrow4c=5d.t\)
\(\Rightarrow5d=2a.t\)
____________________________________________________
\(\Rightarrow2a+3b+4c+5d=2a.t+3b.t+4c.t+5d.t\)
\(\Rightarrow2a+3b+4c+5d=t.\left(2a+3b+4c+5d\right)\)
\(\Rightarrow t=1\)
Khi đó : \(\frac{2a}{3b}+\frac{3b}{4c}+\frac{4c}{5d}+\frac{5d}{2a}=t+t+t+t=1+1+1+1=4.\)
Vậy \(\frac{2a}{3b}+\frac{3b}{4c}+\frac{4c}{5d}+\frac{5d}{2a}=4.\)